Production–living–ecological space transition and its eco-environmental effects based on an improved area-weighted method: A case study of Gangcheng District, a typical industrial base in China - Wei, Yanan; Zhang, Yong; Chen, Longfei; Chen, Hongyan; Zhang, Xueqiang; Liu, Peng (Frontiers in Environmental Science, 2022)
Under the background of rapid social and economic development, it is of great significance to clarify the evolution process of production-living-ecological space (PLES) and its eco-environmental effects for the sustainable utilization of land resources on industrial bases. Based on existing research, it is difficult to accurately measure the differences in eco-environment quality caused by the conversions between land-use types in different years. This paper put forward an improved area-weighted calculation method of the eco-environmental quality index (EQI) and combined the land-use transfer matrix and ecological contribution rate to analyze the eco-environmental effects on typical industrial bases. The results show that the PLES transitions in Gangcheng District were mainly from agricultural production and grassland ecology to forest ecology space, urban living to industrial production space, and grassland ecology to agricultural production space from 2009 to 2020. The improved method can reflect the environmental changes caused by conversions between land-use types in different years. The EQI of agricultural production space increased from 0.373 to 0.388, while the EQI of forest ecology space decreased from 0.810 to 0.739, and the comprehensive EQI increased from 0.441 to 0.470, which showed that the eco-environment quality of the study area was improved on the whole. The conversions of agricultural production and grassland ecology space to forest ecology space were the main factors to improve the eco-environment quality, and the conversions of grassland and forest ecology to agricultural production and agricultural production to industrial production space were the main reasons for the deterioration of eco-environment quality. This paper can contribute to scientific planning of land-use direction, coordination of regional economic and ecological development, and provide case references for similar regions.